Trace metals in polyethylene debris from the North Atlantic subtropical gyre. (February 2019) - Prunier, Jonathan; Maurice, Laurence; Perez, Emile; Gigault, Julien; Pierson Wickmann, Anne-Catherine; Davranche, Mélanie; Halle, Alexandra ter
Abstract: Plastic pollution in the marine environment poses threats to wildlife and habitats through varied mechanisms, among which are the transport and transfer to the food web of hazardous substances. Still, very little is known about the metal content of plastic debris and about sorption/desorption processes, especially with respect to weathering. In this study, plastic debris collected from the North Atlantic subtropical gyre was analyzed for trace metals; as a comparison, new packaging materials were also analyzed. Both the new items and plastic debris showed very scattered concentrations. The new items contained significant amounts of trace metals introduced as additives, but globally, metal concentrations were higher in the plastic debris. The results provide evidence that enhanced metal concentrations increase with the plastic state of oxidation for some elements, such as As, Ti, Ni, and Cd. Transmission electron microscopy showed the presence of mineral particles on the surface of the plastic debris. This work demonstrates that marine plastic debris carries complex mixtures of heavy metals. Such materials not only behave as a source of metals resulting from intrinsic plastic additives but also are able to concentrate metals from ocean water as mineral nanoparticles or adsorbed species. Graphical abstract: Highlights: Plastic debris collected from the North Atlantic subtropical gyre was analyzed for trace metals. It is evidence that plastic oxidation favors the adsorption of some such as As, Ti, Ni, Cd. The presence of mineral particles on the surface of the plastic debris was evidenced by microscopy. Plastics initially contain important amounts of metals resulting from intrinsic plastic additives. Marine plastic debris carry complex mixtures of heavy metals. Abstract : Plastic debris collected from the North Atlantic subtropical gyre was analyzed for trace metals. Marine plastic debris carry complex mixtures of heavy metals but it is evidence that plastic oxidation favors their adsorption.